Study of functions of state, business, third sector and principles of their interaction directed on achievement of effective society - Slyusarenko, Victoria (Technology audit and production reserves, 2017)
The analysis of the functions that the three sectors perform in society: state, business and the third sector has been realized. The principles of relations between them and the principles of cooperation, which help in their effective implementation, have been observed. It is proved that the use of the observed principles: mutual trust and transparency in the relationships; rule of law; human rights, fair competition in economic and social development; mutual recognition of the needs, interests and possibilities will allow Ukrainian society to become effective. The study of the functions, which are performed by participants of tripartism, is important because over fulfillment or under fulfillment leads to distortions, imbalance in development of Ukrainian society and the nation in whole. That is why, we found out that with the help of due consistency that is the functions performed by members of tripartism on the proposed principles we can effectively perform it that is their representatives get an agreed outcome from the process, and it is the indicator of the effectiveness of societies, which is manifested in particular, in effective functioning of: economics, infrastructure, public health have, education and science. These data are important because they indicate a choice of emphasis towards the transformations of society for its effectiveness.